The Characteristics Of Delivery Mothers With Sectio Caesarea At Ha Zaky Djunaid Pekalongan - Lailatul Novia (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Introduction: Children's and mothers' health determines the level of family and community health. The health empowerment success relies on the maternal mortality rate and neonatal mortality rate. The delivery prevalence with the SC method increases around the world by more than 10%-15% as recommended. In Latin America and the Caribbean, the prevalence of section caesarea procedures is high, 40.5%. The data of delivery mothers with Sectio Caesarea at HA Zaky Djunaid Pekalongan reached 100 mothers. Objective: This research revealed the characteristics of delivery mothers with Sectio Caesarea from the perspectives of age, parity, gravida, gestation interval, birth history, and height. Method: This qualitative research is a descriptive retrospective type of research by reviewing the medical records of delivery mothers with section Caesarea.Population: This research population consisted of all delivery mothers with section Caesarea at HA Zaky Djunaid Hospital, Pekalongan City, from July 2023 to August 2023.Sample: The research samples were 100 delivery mothers with Sectio Caesarea taken with total sampling. Results: From the data analysis, the characteristics of delivery mothers with SC, based on age, were mostly 29 years old. Most mothers were multiparity and multigravida. The mothers had SC history with 2-5 years of gestational interval. Most mothers were 148cm high.